DEVELOPMENT OF INTERACTIVE POWERPOINT ASSISTED LEARNING MEDIA TO IMPROVE STUDENT LEARNING OUTCOMES ON THE BEAUTIFUL THEME OF TOGETHERNESS IN CLASS IV SDN 157013 SIBABANGUN 5, CENTRAL TAPANULI REGENCY - Nurhanifa Tamba; Reh Bungana Br. Perangin-angi; Yusnadi Yusnadi (SENSEI RESEARCH CENTER, 2021)
This study aims to develop instructional media software to determine the feasibility and effectiveness of instructional media in improving student learning outcomes in the sub-theme of the Beauty of Togetherness. Researchers used media, namely interactive powerpoints in the design and development of instructional media. This type of research is research and development (R & D). The effectiveness of Interactive multimedia based on the test of learning outcomes, namely the completeness of individual learning results data in class IV-A using interactive powerpoints on the beautiful theme of togetherness, obtaining an average score of 88.64% of 22 students stated that all students are complete and in class IV-B who use teaching materials for the theme of the beauty of togetherness obtained an average score of 75, 68% of 22 students declared 18 students completed and 4 students declared incomplete. Based on the results of the validator's assessment on the material expert, it is feasible to reach 4.45 with the very feasible category. Media experts get 4.50 in the very feasible category and design experts get 4.83 in the very feasible category. From the validation results, the feasibility of interactive powerpoint media is very feasible to use. The results of the difference test analysis showed that From the validation results, the feasibility of interactive powerpoint media is very feasible to use. The results of the difference test analysis showed that From the validation results, the feasibility of interactive powerpoint media is very feasible to use. The results of the difference test analysis showed thatt count> t table (1.728> 1.688)at the significant level (0.05) with the conclusion that Ha is accepted and Ho is rejected. This proves that interactive powerpoints are more effectively used and verified in improving student learning outcomes on the theme of the beauty of togetherness in Class IV SDN 157013 Sibabangun 5, Tapanuli Tengah Regency